MANGGIS DALAM LUKISAN REALIS KONTEMPORER - AFRI ARIN QURNIATY, Yasrul Sami, S.Sn., M.Sn. (Serupa The Journal of Art Education, 2019)
The creation of this final work aims to convey about the crisis the value of honesty in the realm of  leadership that makes mangosteen a symbol of honesty. Through several stages of the method and  process of work that are passed: (1) preparation, (2) Elaboration, (3) Synthesis, (4) Realization of  the Concept, (5) Completion. The manifestation of the visualization of the final work of mangosteen in contemporary realist paintings entitled : (1) Tertinggal, (2) Dikendalikan , (3) Manggis dan Uang,  (4) Manggis dan Uang#2, (5)Sengaja,(6) Kejam,(7) Batas,(8) Pecah,(9) Rapuh, (10) Keras.Keywords: mangosteen, exploration, visual.